GENERAL SOLUTION OF QUADRATIC EQUATIONS IN FREE GROUPS - Markanin, G.S.; Malkhasyan, A.Sh. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2015)
The general solution of quadratic equations in free group using an automat, specified by the certain oriented graph is presented.
Keywords: quadratic equation, free group, equation in free semigroup